(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: The challenges faced by mothers during caring for children with ASD are a risk factor for maternal mental health problems. One effort to maintain the mental health of the mothers who have children with ASD is to ensure the availability of social support. Aim: The aim of this study is to determine the correlation between social support and mental health among mothers of children with ASD. Method: This was a descriptive study with a cross-sectional approach. Eighty (80) mothers of children with ASD were selected as the respondents in this study using purposive sampling method. Bantul and Kulon Progo Regencies were chosen as the research locations. The Multidimensional Scale of Perceived Social Support (MSPSS) and General Health Questionnaire-12 (GHQ-12) were used to measure the social support and maternal mental health. The Spearman test was used to see the correlation between social support and maternal mental health problems. Results: The results show that social support and maternal mental health problems have a significant correlation (p=0.03; r=- 0.23). The univariate test shows that 44% of mothers of children with ASD indicate psychological disorders. Conclusion: There is a correlation between social support and mental health among mothers of children with ASD.